Flight experiments on the effects of step excrescences on swept-wing transition. (1st January 2014) - Duncan, Glen T.; Crawford, Brian K.; Tufts, Matthew W.; Saric, William S.; Reed, Helen L.
A 30° swept-wing model with a movable, leading-edge extending to 15% chord is used in flight tests to study the effect of two-dimensional, step excrescences on swept-wing transition, where stationary-crossflow waves are typically the dominant instability. Transport unit Reynolds numbers are achieved using a Cessna O-2A Skymaster. Forward- and aft-facing steps are modulated in-flight. Pressure measurements are compared with CFD. Infrared thermography is used to globally detect boundary-layer transition. When the 2-D pressure gradient matches the unswept case, the swept-wing case has a lower Rekk, crit . However, there is still potential to relax conventional, laminar-flow tolerances for steps.